TOURING THE GAP BETWEEN EXTENSION AGENTS, EXTENSION STRATEGIES, CAPACITY BUILDING AND CONSTRAINTS OF RICE PRODUCTION IN AGRICULTURAL ZONE IN NIGER STATE, NIGERIA - Mohammed, U.; Umaru, A.; Ahmad, B. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2022)
The study examined or assessed the gap between extension agents, extension strategies, capacity buildinga and constraints of rice production in agricultural zone of Niger State, Nigeria. Multi-stage sampling technique was used in selecting 48 respondents. Data were collected through the administration of questionnaire and analyzed using descriptive statistics. The study found that a participatory approach is not fully decentralized in planning, monitoring and evaluation of the agricultural extension programs to meet the demand-driven services of the farmers in the study area. Moreover, there is a difference between the capacity building of the extension personnel and the constraints incurred in rice production. The capacity building is mostly focused on production and post-harvest of rice production, while having multitude of constraints in marketing as well. Therefore, it is recommended that a participatory approach must be fully promoted and the capacity building of extension personnel must be melded with the demand-driven needs of farmers in approaching the rice production issues. The study will be needful for extension agents, policymakers, researchers, educationists and stakeholders in Agriculture and non-Agricultural sectors so as to understand ways of increasing the quality and effectiveness of agricultural extension services to foster agricultural production.